2016
DOI: 10.3390/molecules22010067
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Phytochemical Investigation, and Safety Evaluation of Chlorogenic Acid Products from Eupatorium adenophorum

Abstract: Eupatorium adenophorum is widely distributed throughout the world’s tropical and temperate regions. It has become a harmful weed of crops and natural environments. Its leaves contain bioactive compounds such as chlorogenic acid and may be used as feed additives. In this study, chlorogenic acid was extracted and separated from leaves of E. adenophorum. Three chlorogenic acid products were prepared with different purities of 6.11%, 22.17%, and 96.03%. Phytochemical analysis demonstrated that the main toxins of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Used as an anti-inflammatory, blood coagulant, antimicrobial, antiseptic, and analgesic, antipyretic. Isomers of mono-caffeoylquinic acid present in E. adenophoium exhibit potent anti-inflammatory, anti-bacterium, and anti-obesity properties [50].…”
Section: Eupoterium Adenophoium Asteraceaementioning
confidence: 99%
“…Used as an anti-inflammatory, blood coagulant, antimicrobial, antiseptic, and analgesic, antipyretic. Isomers of mono-caffeoylquinic acid present in E. adenophoium exhibit potent anti-inflammatory, anti-bacterium, and anti-obesity properties [50].…”
Section: Eupoterium Adenophoium Asteraceaementioning
confidence: 99%
“…A statistical analysis conducted by Tajabadi et al [ 15 ] found that 70% of the 15,822 scaffolds belonging to natural products (NPs) are non-flat and represent an interesting resource for the design of new synthetic molecules [ 16 ]. Among such saturated ring systems, the pyrrolidine moiety is represented widely in NPs, especially in alkaloids isolated from plants or microorganisms [ 17 19 ] (Fig. 2 ) showing different biological activities, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…(Cao et al, 2020; Wang et al, 2018). Researchers have demonstrated the antioxidant and antitumour effects of CGA; it also exhibits a therapeutic effect on type II diabetes mellitus (Gao et al, 2019; Kang et al, 2013; Williamson, 2020), and its safety has been proven (Amano et al, 2019; Liu et al, 2016). In addition, CGA exerts an anti‐inflammatory effect by inhibiting NF‐κB and p38 signalling pathways and the release of reactive oxygen specific (Chen et al, 2018; Palócz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%